Gambaran Faktor Risiko pada Wanita Hamil Trimester 3 yang Terkonfirmasi Positif SARS-CoV-2 - Aurelia S. Posumah; Mayer F. Wowor; Glady I. Rambert (eBiomedik, 2021)
Abstract: Coronavirus Disease 2019 (COVID-19) a infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). There are several groups that are susceptible to infection with SARS-CoV-2, one of which is pregnant women. This can be attributed to changes in the physiology and immune system that occur in pregnant women. This study aimed to determine the most risk factors that cause pregnant women in Prof. Dr. R. D. Kandou was infected with SARS-CoV-2. This type of research is descriptive with a retrospective approach, using secondary data in the form of data from the patient's medical record status. From 5 patients studied, there were 4 patients with risk factors for hypertension (80%) and 1 patient with close contact risk factors (20%), but other risk factors such as diabetes mellitus, travel history in transmission areas, obesity and smoking are not found. In conclusion, from 5 patients studied, the most risk factor that causes pregnant women in the third trimester to be infected with SARS-CoV-2 is hypertension (80%).Keywords: 3rd trimester pregnant women, SARS-CoV-2, risk factorÂ Â Abstrak: Coronavirus Disease 2019 (COVID-19) penyakit menular yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Terdapat beberapa kelompok yang rentan terinfeksi SARS-CoV-2, salah satunya wanita hamil. Hal ini dapat dikaitkan dengan perubahan fisiologi dan sistem imunitas tubuh yang terjadi pada wanita hamil. Tujuan penelitian ini untuk mengetahui faktor risiko terbanyak yang menyebabkan wanita hamil di RSUP Prof. Dr. R. D. Kandou terinfeksi SARS-CoV-2. Jenis penelitian yang digunakan bersifat deskriptif dengan pendekatan retrospektif, yaitu menggunakan data sekunder berupa data dari status rekam medik pasien. Dari 5 pasien yang diteliti, didapatkan 4 pasien dengan faktor risiko hipertensi (80%) dan 1 pasien dengan faktor risiko kontak erat (20%), namun pada faktor risiko lain seperti diabetes melitus, riwayat perjalanan di daerah transmisi, obesitas dan merokok tidak ditemukan. Sebagai simpulan, dari 5 pasien yang diteliti, faktor risiko terbanyak yang menyebabkan wanita hamil trimester 3 terinfeksi SARS-CoV-2 adalah hipertensi (80%).Kata Kunci: wanita hamil trimester 3, SARS-CoV-2, faktor risiko